Situs Rumah Sandi: Sumber Pembelajaran Geometri Transformasi Berdasarkan Pendekatan Etnomatematika - Dinahyu Arifah Yuniar; Muhammad Prayito; Nurina Happy (Departement of Mathematics Education, 2024)
This research aims to explore the understanding of ethnomathematics through the cultural context of the Rumah Sandi site in teaching transformation geometry mathematics. Ethnomathematics serves as a bridge between mathematics and culture, providing a valuable learning reference for students. The Rumah Sandi site holds historical significance as a monument of resistance during the Dutch Military Aggression II. In 2014, it underwent renovation by the Sandi Negara Institution and was renamed